3D flow simulation of a baffled stirred tank for an assessment of geometry simplifications and a scale-adaptive turbulence model. (15th February 2021) - Rave, Kevin; Lehmenkühler, Martin; Wirz, Dominic; Bart, Hans-Jörg; Skoda, Romuald
Highlights: Benefits of scale-adaptive (SAS) over URANS turbulence models are highlighted. Even on relatively coarse grids, SAS is advantageous over URANS. Mean velocity and turbulence prediction is significantly improved by SAS. Utilization of a full 360° domain is essential to capture macro-instabilities. Consideration of real blade thickness improves accuracy for SAS. Abstract: Flow simulations are performed on single-phase flow in a baffled tank stirred by a Rushton turbine at a Reynolds number of 40 000 . The flow physics are discussed, and the benefits of a scale-adaptive simulation (SAS) compared with classical unsteady Reynolds-averaged Navier-Stokes (URANS) models are highlighted. The effect of geometry simplifications, i.e., infinitely thin blades, is illustrated. Furthermore, due to the existence of low-frequency flow instabilities, the necessity of utilizing a full 360 ° computational domain and the consideration of up to 150 impeller revolutions in the simulation is demonstrated. By a zonal grid refinement within the blade and wake region, the successively resolved portion of the turbulent spectrum is investigated. Even on computational grids typically employed for URANS simulations, the SAS shows a considerably improved prediction of mean velocity and turbulence statistics, compared with conventional URANS models, and should thus be preferred, e.g., to an under-resolved large eddy simulation (LES).